Evaluation of serum levels of c-reactive protein after total knee arthroplasty in patients with rheumatoid arthritis - Vilella, Bruno; Vieira, Marco Túlio C.; Faria, José Leonardo R. de; Barretto João Maurício; Albuquerque, Rodrigo S. Pires e; Loures, Fabrício B. (Brazilian Journal of Health and Biomedical Sciences, 2022)
Objective: The objective of this study is to evaluate the serum levels of C-reactive protein in the first three weeks after total knee arthroplasty, in patients with knee osteoarthritis secondary to rheumatoid arthritis and a control group. Methods: This is a prospective study evaluating 30 patients with knee osteoarthritis secondary to rheumatoid arthritis who underwent total knee arthroplasty between January 2015 and March 2017. A control group of patients submitted to total knee arthroplasty by primary osteoarthritis was created with data from the institution’s database. The proportion was of three controls for each case and the criteria used for pairing were age, gender, ethnicity and body mass index. Serum C-reactive protein was measured on the day before, and on the third and twenty-first days after the procedure in all patients. Results: No statistically significant changes were found between the case and control groups for the C-reactive protein levels evaluated nor their variations. The results suggest that the presence of rheumatoid arthritis does not interfere in the postoperative response of C-reactive protein. Conclusion: The serum values of C-reactive protein after TKA do not differ between patients with primary or secondary osteoarthritis to RA. Thus, the reference values can be considered equal in both cases.